HUBUNGAN TINGKAT KEPATUHAN MINUM OBAT TERHADAP KADAR GULA DARAH PASIEN DM TIPE 2 DI PUSKESMAS PEKAUMAN BANJARMASIN - Hasniah; Kurnia, Ina; Ramadhani, Juwita (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
One of the most important factors in the treatment of Type 2 diabetes mellitus (type 2 diabetes mellitus) is the degree of patient compliance with the rules of its treatment. The degree of adherence of Type 2 DM patients to treatment guidelines has a significant impact on the stability of blood sugar levels. The purpose of this study was to determine the relationship of drug adherence to blood sugar levels of patients with Type 2 diabetes in Pekauman Banjarmasin Health Center. This study was conducted using observational analytical methods with cross-sectional design, data collection was carried out prospectively in February-April 2024 with a sample of 76 respondents. Data obtained from interviews and questionnaires. The instrument used for medication adherence using the questionnaire Morisky Medication Adherence Scale (MMAS-8). The relationship between the level of compliance of patients with blood sugar levels was analyzed using a statistical chi-square test. The results showed that there was a significant relationship between the level of patient compliance with blood sugar levels with the value (P = 0.000). The conclusion of this study is that adherence to medication is an important role in the management of treatment in patients with Type 2 diabetes mellitus at the Pekauman Banjarmasin Health Center.